The NF-YC–RGL2 module integrates GA and ABA signalling to regulate seed germination in Arabidopsis - Xu Liu (Nature Portfolio, 2016)
Crosstalk between gibberellic acid (GA) and abscisic acid (ABA) regulates seed germination. Here the authors show that NF-YC transcription factors can interact with the RGL2 DELLA protein to regulate expression of ABI5and therefore modulate ABA- and GA-responsive gene expression.